COMPARISON OF THE FINANCIAL PERFORMANCE OF MICRO AND SMALL BUSINESSES BEFORE AND AFTER GET FINANCIAL ASSISTANCE AT MICRO AND SMALL ENTERPRISES OF JEKA MEMBERS - Karim Budiono; Yulia Anggraeni; Ratih Rachmawati; Amar Subagyo (LPPM Institut Teknologi dan Sains Mandala, 2023)
This study aims to determine whether there is a significant difference between the financial performance of JEKa member SMEs before and after receiving financial assistance. The population in this study were 109 members of SMEs of JEKa Jember. The data analysis method used were a descriptive quantitative percentage and the Manova test. The results showed that there was a significant difference between the financial performance of SMEs members of JEKa Jember before and after receiving financial assistance interms of Liquidity Ratios (CRR, QR, CR), Solvency Ratios (DTAR, DER), Rentability Ratios (PM, NPM, GPM, ROI, ROA) and there is no significant difference between the financial performance of JEKa member SMEs before and after receiving financial assistance in terms of Activity Ratios (ITR, RTR, FATO, TATO)